On born’s conjecture about optimal distribution of charges for an infinite ionic crystal - Bétermin, Laurent; Knüpfer, Hans (Journal of nonlinear science, 2018)
We study the problem for the optimal charge distribution on the sites of a fixed Bravais lattice. In particular, we prove Born’s conjecture about the optimality of the rock salt alternate distribution of charges on a cubic lattice (and more generally on a d-dimensional orthorhombic lattice). Furthermore, we study this problem on the two-dimensional triangular lattice and we prove the optimality of a two-component honeycomb distribution of charges.
Gesehen am 17.12.2018